Microbial dynamics and flavor formation during the traditional brewing of Monascus vinegar - Jiang, Yajun; Lv, Xucong; Zhang, Chong; Zheng, Yimei; Zheng, Baodong; Duan, Xu; Tian, Yuting (Food research international, 2019)
Monascus vinegar is one of the most famous and popular Chinese vinegars. The present study identified 60 volatile compounds, 23 amino acids, and seven organic acids during the traditional brewing of Monascus vinegar. Acetic acid, alanine, alcohols, esters, lactic acid, and valine were the predominant metabolic compounds found during the fermentation process. Komagataeibacter medellinensis, Lactobacillus acetotolerans, Saccharomycopsis fibuligera, Sterigmatomyces halophilus, and Yarrowia lipolytica were the dominant microorganisms during the traditional brewing of Monascus vinegar. Furthermore, based on Spearman's correlation analysis, K. medellinensis showed a positive correlation with acetic acid, acetoin, benzaldehyde, phenethyl acetate, 4-ethylphenol, proline, threonine, and isoleucine. Saccharomyces cerevisiae was positively associated with the production of acetoin, benzeneacetaldehyde, 2,3,5-trimethylpyrazine, proline, threonine, and isoleucine. Bacillus velezensis and Yarrowia lipolytica were positively correlated with esters and alcohols, implying that these microorganisms might make a significant contribution to the flavor of vinegar. These findings demonstrated that some microorganisms may play important roles in improving the aromatic quality of Monascus vinegar. [Display omitted] •Volatile compounds in Monascus vinegar were identified.•Amino acids and organic acids in Monascus vinegar were investigated.•Flavor and dominant microflora network analysis in vinegar were explored.